Evaluasi Implementasi Pengelolaan Piutang BPJS di BLUD Rumah Sakit Umum Daerah Provinsi Nusa Tenggara Barat - Alisza Novrita Sari; Erliany Syaodih; Yuniati Lestari (Journal Of Business, Finance, and Economics (JBFE), 2025)
The Regional General Hospital (RSUD) of West Nusa Tenggara Province, as a major referral hospital, faces a serious issue of accumulated receivables from the National Health Insurance Agency (BPJS Kesehatan) due to claim payment delays of 60–120 days. This situation strains cash flow and affects drug procurement, medical staff remuneration, and service continuity. This study aims to evaluate the management of BPJS receivables and their impact on the hospital’s financial and operational conditions, as well as to formulate improvement strategies. A qualitative descriptive method was employed through interviews, observation of claim submission processes, and document review. The analysis covered receivable conditions, claim procedures, management strategies, operational impacts, and recommendations. The results indicate challenges related to incomplete medical records, limited coding personnel, and the lack of integration between the hospital information system and the BPJS e-Claim application, which lengthen receivable periods and weaken cash flow. Management efforts such as establishing a claim team, administrative digitalization, and routine coordination with BPJS have reduced claim rejection risks. Recommendations include strengthening electronic medical records, enhancing human resource capacity, integrating the hospital information system with BPJS applications, and conducting regular evaluations using average collection period and receivables turnover ratio to improve receivable management effectiveness and ensure service sustainability.